PENERAPAN MODEL PEMBELAJARAN DIRECT LEARNING GUNA MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII MTs SABILUNNAJAH PATUMBAK DELI SERDANG - Gajah, Ewin Sanjaya; Ponidi, Ponidi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
Reading and writing skills for a teacher are very important skills to be mastered by every student. So that this is used as a background by the teacher in carrying out classroom actions. In addition, low student learning outcomes in Indonesian subjects make it a reference for teachers to conduct research in order to improve student learning outcomes in class VIII in Indonesian subjects. The purpose of this classroom action research is to improve the learning outcomes of class VIII students in Indonesian subjects at MTs Sabilunnajah Patumbak Deli Serdang by using the Direct Learning learning model. This research process goes through stages that begin with the pre-cycle, Cycle I and Cycle II. The results of the research carried out in class VIII of MTs Sabilunnajah Patumbak Deli Serdang experienced changes in increasing student achievement. The increase itself can be seen from the level of complete learning of students who reach the KKM. This can be seen in the pre-cycle stage, the level of completeness only reached 47% or only 9 students completed, and experienced an increase in learning mastery in the first cycle to 63% or only 12 students completed, and again experienced an increase in mastery in the second cycle which reached 89%. or 17 students who completed. The data from this research shows that classroom action research using the Direct Learning learning model is able to improve student achievement in Indonesian lessons.Â